To Act or not to Act: How Coleridge Changed the Way We See Hamlet - Poštić, Svetozar (Respectus Philologicus, 2014)
Exactly 200 years ago, from 1811 to 1819, Samuel Taylor Coleridge, one of the most famous English Romantic poets, held a series of influential lectures about William Shakespeare and his plays. His presentation of “Hamlet”, a play hitherto not only negatively appraised, but even viewed quite negatively by the leading critics, most notably Samuel Johnson, was especially significant. His insightful analysis helped to change the general opinion about the play, and pointed to the qualities of “Hamlet” that made it into perhaps the best known and most frequently played drama in the next 200 years. In this paper, I examine the way Coleridge was able to recognise the neglected features of Shakespeare’s profound tragedy up to that point. First of all, he identified with the main protagonist of the play, the Prince of Denmark, and described the unbridgeable gap between ambitions and power of imagination on the one hand, and inability to act on the other. Like Hamlet, Coleridge had "great, enormous, intellectual activity, and a consequent proportionate aversion to real action" (Coleridge 2014: 345). Aware of this shortcoming, but unable to correct it, the extremely talented and educated Coleridge presented it in fascinating detail. Secondly, he used his knowledge of the most influential contemporary philosophers, especially Kant, Locke and Hobbes, and the increasingly popular psychological approach to character analysis in order to paint an internal portrait of leading characters of the play. Due to the increasingly popular trend in recent literary theory and analysis focusing on the political and material context of an art work, the universal qualities of Coleridge’s intepretation of “Hamlet” that contributed to the lasting influence of his critique have been largely neglected. This article intends, therefore, to re-establish the significance of Coleridge’s “Hamlet” lectures